(untitled) (Fiep Bulletin - online, 2014)
The physical activity is now a priority in the Public Health. One of the declared primordial factors of comment on the physical inactivity, is the prevalence of sedentarismo and behaviors of risks to the health, in part, decurrent of the inexistence of one politics of monitoring epidemiologist focusing the exposition of risk behaviors. Where the estimate of insufficiently active brazilian adults would arrive approximately 60%. In Brazil, it is made use of few data on the prevalence of sedentarismo in the different ages groups, with this, has a great difficulty to evaluate the behavior how much to the practical one of physical activities due to lack of standardized instruments and with good level of precision for use in population studies and different social and cultural contexts. Objective: The study had as objective to analyze and to correlate the level of physical activity, IMC and RCQ of people with age above of 15 years. Methodology: It is a descriptive research of inquiry, which had to the data-collecting without, however, intervening with the study object. The study used as citizens 110 female individuals, living of the city of Rio de Janeiro that have above of 15 years. For analysis of the level of physical activity the short versio of IPAQ (International Questionnaire of Physical Activity) was used as instrument. Used in diverse places, including Brazil, where it was validated in short and long versions (CRAIG, 2003). For the calculations of IMC (Index of Corporal Mass), the protocol of Quetelet was used and the protocol for calculation of RCQ (Relação Cintura Quadril). The questionnaires were given to the individuals with age above of 15 years, which had to be filled and given back soon after that in the same place. Techniques of descriptive statistics for analysis of the data had been used. Results: The data had demonstrated to percentile greater of active individuals in all the searched ages bands. The IMC in the age between 15 and 30 were bigger in the very active people, and the RCQ, was bigger in active people. Between 30 and 60 years, IMC and the RCQ were bigger in insufficiently active people. In people above of 60 years, was found IMC greater in active individuals, and bigger RCQ in very active individuals. Conclusion: Through the analysis of the presented data RCQ can be concluded that the association between the level of physical activity, IMC and RCQ does not exist.